# (x-3y)squared=

## Simple and best practice solution for (x-3y)squared= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (x-3y)squared= equation:

Simplifying
(x + -3y) * squared = 0
Reorder the terms for easier multiplication:
Solving
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), 'adeqrsu'.
Subproblem 1Set the factor 'adeqrsu' equal to zero and attempt to solve:
Simplifying
Solving
Move all terms containing a to the left, all other terms to the right.
Simplifying
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(x + -3y)' equal to zero and attempt to solve:
Simplifying
x + -3y = 0
Solving
x + -3y = 0
Move all terms containing a to the left, all other terms to the right.
Add '-1x' to each side of the equation.
x + -1x + -3y = 0 + -1x
Combine like terms: x + -1x = 0
0 + -3y = 0 + -1x
-3y = 0 + -1x
Remove the zero:
-3y = -1x
Add '3y' to each side of the equation.
-3y + 3y = -1x + 3y
Combine like terms: -3y + 3y = 0
0 = -1x + 3y
Simplifying
0 = -1x + 3y
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`